Perceptions of educational leaders about creating e-portfolios as part of a leadership upskilling program - Zeina Hojeij; Areej ElSayary (Institute of Advanced Engineering and Science, 2026)
The effectiveness of e-portfolios in supporting educator professional development (PD) remains uncertain, particularly in demonstrating leadership skills through reflections and perceptions. This study investigates the utility of e-portfolios by examining the perspectives of educational leaders within a K-12 setting in the United Arab Emirates (UAE). The study involved 17 participants who completed an upskilling program, creating digital portfolios as part of their training. Additionally, 10 participants engaged in semi-structured interviews. The findings revealed three primary themes: genuine professional leadership growth, continuous PD, and an enhanced understanding of the student learning experience. The creation of e-portfolios not only fostered authentic PD but also served as a catalyst for ongoing growth, self-discovery, and continuous learning. This research concludes that e-portfolios are valuable tools for PD, promoting reflective practice and lifelong learning among educational leaders.